Pengaruh Brand Image Dan Kualitas Produk Terhadap Keputusan Pembelian Busana Muslim Pada Member Rabbani Jombang - Indah Nur Azizah; Lilis Sugi Rahayu Ningsih (CV. ALIM'SPUBLISHING, 2023)
Brand Image or can be called Brand Image is a perception of a brand Brand about the brand associated with brand associations that appear in the minds of consumers. One of the factors that can affect the brand image of a company's product is quality. Quality related to product quality offered by manufacturers with a particular brand. The purpose of this study was to determine whether brand image and product quality variables significantly influence purchasing decisions of Rabbani members in the city of Jombang. This research uses quantitative research using descriptive statistics, validity test, reliability test, classic assumption test, partial and simultaneous hypothesis test, and coefficient of determination with the help of the IBM SPSS Statistics 20 program. The number of samples is 110 Rabbani members in Jombang. Data collection uses a non-probability sampling technique by means of purposive sampling. Data collection was carried out by distributing questionnaires. The results showed that (1) brand image has an effect on purchasing decisions (2) product quality has an effect on purchasing decisions (3) brand image and product quality has an influence on purchasing decisions. Keywords: Brand Image, Buying Decision, Product Quality